Memperkuat Otonomi Daerah: Gagasan Memperbarui Regulasi Barang Milik Daerah - Ramadhan, Febriansyah; Prasada, Dewa Krisna; Abhiseka, I Gede Druvananda (Hang Tuah Law Journal, 2025)
The administration of regional property via usage programs constitutes a source of regional financial Revenue. The administration of regional property is governed by Government Regulation Number 1 of 2014 about the Management of State/Regional Property, subsequently supplemented by Regulation of the Minister of Home Affairs Number 19 of 2016 on the Management of Regional Property. Nonetheless, the regulation of the regional property (Barang Milik Daerah/BMD) sector encounters numerous challenges, particularly regarding the coordination required between the Minister of Home Affairs and the Minister of Finance in developing general and technical policies on regional property, which remains suboptimal. Consequently, the Minister of Home Affairs Regulation Number 19/2016 remains inadequate as a regional reference for formulating Regional Regulations/Regulations of Regional Heads, leading many to directly consult the Minister of Finance, which governs State Property. According to the description above, the subsequent challenges are articulated: Issues in regulating the regional property sector at both central and regional levels. Format for the Reorganization of the Central Regulation of the Regional Public Property Sector. Normative (legal) research methodologies, including statutory, conceptual, and case approaches, are employed to analyze the problem formulation. Findings from this research: Regulatory issues arise from a lack of alignment among ministries in coordinating efforts. The Minister of Home Affairs reports to the Coordinating Minister for Political, Legal, and Security Affairs, whereas the Coordinating Minister for the Economy oversees the Minister of Finance. The organization of rules involves distinguishing between Government rules for state property and regional property, necessitating cross-sectoral harmonization throughout their formulation. This must be accomplished due to the control of regional property under many laws, necessitating harmonization in formulating technical regulations at the governmental level, along with heightened care. Recent legislation must be modified to align overarching policies and their technical execution.